Exploring Biblical Women in Music - Leneman, Helen (The Oxford handbook of feminist approaches to the Hebrew Bible, 2020)
This essay explores various musical works that retell the stories of biblical women who are largely silent in the biblical text. It analyzes operas and oratorios featuring biblical women with prominent roles in more than one musical work. These are: Sarah, Hagar, and Rebecca in the book of Genesis; Jochebed, Pharaoh’s daughter, and Miriam in the book of Exodus; and Michal and Bathsheba in the books of Samuel. This research draws on my previous scholarship on nineteenth- and twentieth-century opera, oratorio, and song settings of biblical women. Many musical settings of biblical narratives focus intensely on the women. The women’s singing voices add new elements to their depictions, and librettos almost always enlarge the women’s roles. Composers and librettists together turn the women into three-dimensional characters. The essay presents various threads in numerous musical works that tie together the re-visioning of several biblical women. The goal is to illustrate how the selected women move from the biblical background to the musical foreground, and to offer new and surprising perspectives on biblical women.